Analytical technique for self-absorption structure of iron L-emission spectra obtained by soft X-ray emission spectrometer. (17th February 2022) - Yokoyama, Takaomi D; Takahashi, Hideyuki; Koshiya, Shogo; Murano, Takanori; Terauchi, Masami
Abstract: The method deriving the L self-absorption spectrum from L α, β emission spectra obtained at different accelerating voltages has been optimized for analyzing the chemical state of Fe in solid materials. Fe L α, β emission spectra obtained are fitted using Pseudo-Voigt functions and normalized by the integrated intensity of each Fe L l line, which is not affected by L 2, 3 absorption edge. The self-absorption spectrum is calculated by dividing the normalized intensity profile collected at low accelerating voltage by that collected at a higher accelerating voltage. The obtained profile is referred to as soft X-ray self-absorption structure (SX-SAS). This method is applied to six Fe-based materials (Fe metal, FeO, Fe3 O4, Fe2 O3, FeS and FeS2 ) to observe different chemical states of Fe in those materials. By comparing the self-absorption spectra of iron oxides, one can observe the L 3 absorption peak structure shows a shift to the higher energy side as ferric (3+) Fe increases with respect to ferrous (+2) Fe. The intensity profiles of self-absorption spectra of metallic Fe and FeS2 shows shoulder structures between the L 3 and L 2 absorption peaks, which were not observed in spectra of Fe oxides. These results indicate that the SX-SAS technique is useful to examine X-ray absorption structure as a means to understand the chemical states of transition metal elements.